A Suprema Corte como modelo de razão pública a partir de John Rawls - Tramontini, Pierre (Universidade do Vale do Rio dos Sinos, 2019)
Justice as fairness, a theory conceived by John Rawls, presupposes a political conception of principles related to the ideal of social cooperation and is instrumented by solving issues pertaining to political-liberal systems. In idealizing the conception of justice in which ordinary judgments are formulated according to principles, it assumes that individuals share an equal citizenship, considering the social nature, the autonomy of the citizen himself and the existence of diverse doctrines. John Rawls recognizes the need to establish political power to organize social relations in the face of reasonable pluralism, given that political values, reflected in the principles of justice, will shape a constitutional democracy. Based on the assumption that society is composed of several comprehensive doctrines and, given the existence of different judicial decisions for similar cases, it is essential to establish a north, dismissed of individual positions, able to guide those who hold the interpretative competence for apply the rule to the specific case and, thus, promote justice. On rawlsian theory, public reason presents itself as the guiding thread that enables constitutional democracy to recognize rights and to legitimize the political formation of public institutions and, if internalized by individuals, will ensure to all the possibility of access and effective use of the freedoms and opportunities that are inherent to it, advocated as principles of justice. Faced with the difficulty of achieving a almost justice social situation, such as Rawls's ideology, this way of acting as a special type of political appeal is not justified until measures are taken within the legal framework. Therefore, being the conflicts between members of this society unavoidable, the natural consequence, in order to guarantee the stability of social relations, is the search for a point of equilibrium, and this ends in the Judiciary, especially in the Supreme Court. This court plays an important role in deciding, on the basis of the ideal of justice, in order to harmonize social conflicts, ensure stability and achieve legal certainty. It is for this Power, therefore, besides assigning meaning to the law, to make it adapted to reality, and this is done through judgments endowed with authority on fundamental political issues, from a clear, effective interpretation of the Constitution and that reflects the public reason. By focusing on Rawls's teachings and, at the same time, analyzing historical decisions of the Brazilian Federal Supreme Court, it was tried to understand the importance of adopting reasonableness as the decision-making power and the social-political consequences of judicial positions that reflect public reason.
Keywords: Justiça como Equidade; Razão Pública; Decisões Judiciais; Suprema Corte; John Rawls; Justice as Fairness; Public Reason; Judicial Decisions; Supreme Court; John Rawls; ACCNPQ::Ciências Humanas::Filosofia